2009
DOI: 10.2133/dmpk.24.180
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in Skin of Ceramide after Oral Administration to Rats

Abstract: In this study, the absorption, distribution and excretion of ceramide were examined in rats. After a single oral administration of (3)H-ceramide, mean plasma concentration of radioactivity reached maximum at approximately 10.67 hr and decreased with a T(1/2) of 67.12 hr. The mean cumulative excretion of radioactivity in urine and feces accounted for approximately 4.79% and 87.44%, respectively, of the dose. At 96 hr after dosing, 1.67% and 3.67%, respectively, of the dose were still present in the skin and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 11 publications
0
31
1
Order By: Relevance
“…In this study, the total recovery of sphingosine in an intact form after administration of glucosyl-N-palmitoylsphingosine was lower than reported in other studies, which used labeled sphingolipids ( 42 ), because most of the dietary sphingosine is converted to palmitic acid in the intestinal mucosa and is incorporated into chylomicron the predominant structure of sphingoid bases in higher plants, can be absorbed into the lymph by intestinal cells after administration of maize glucosylceramide, but the recovery is extremely low. A large portion of the 4,8-sphingadienine absorbed by intestinal cells is a constituent of complex sphingolipids, including at least ceramide, while the smaller portion is in the free form in the lymph.…”
Section: Discussioncontrasting
confidence: 71%
“…In this study, the total recovery of sphingosine in an intact form after administration of glucosyl-N-palmitoylsphingosine was lower than reported in other studies, which used labeled sphingolipids ( 42 ), because most of the dietary sphingosine is converted to palmitic acid in the intestinal mucosa and is incorporated into chylomicron the predominant structure of sphingoid bases in higher plants, can be absorbed into the lymph by intestinal cells after administration of maize glucosylceramide, but the recovery is extremely low. A large portion of the 4,8-sphingadienine absorbed by intestinal cells is a constituent of complex sphingolipids, including at least ceramide, while the smaller portion is in the free form in the lymph.…”
Section: Discussioncontrasting
confidence: 71%
“…The purpose of this double-blind randomized controlled human clinical trial was to test, in a rigorous way, the hypothesis that even small amounts of sphingoid base derivatives, administered orally to humans, can afford measurable and significant and perceivable benefits to the skin, as suggested by the various animal studies and a few smaller-scale human trials [9][10][11][12][13][14][15][16][17] and our own preliminary study.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a large proportion of ingested sphingolipids are excreted in the feces, animal studies reported that after oral intake radiolabeled ceramides are metabolized, absorbed and distributed to many tissues, including the skin. In rats, orally administered radiolabeled ceramides were shown to be delivered to the epidermis [10]. In another study on mice, after administration of 13 C-labeled dihydroceramides, their metabolite 13 C-labeled sphinganine was clearly detected in the skin, liver, skeletal muscle and synapse membrane in the brain [11].…”
Section: Introductionmentioning
confidence: 99%
“…As plant-derived CERs are chemically similar to epidermal CERs, phytoCER-based skincare products can aid in skin moisturization and protective barrier reinforcement. Oral as well as topical delivery of phytoCERs can either enhance the endogenous epidermal lipid-synthetic capability [16,98] or replace depleted skin CERs in some skin conditions and ageing [99]. These CERs are naturally found in many cereal, tuber, and legume dietary sources such as wheat [74,77,84], rice [73,80,100], corn [80,101], potato and sweet potato [96], soybean [77,102], and konjac [103,104].…”
Section: Plants Commonly Used In Phytocer-based Formulationsmentioning
confidence: 99%